PAIN CHARACTERISTICS OF CENTRAL NERVOUS SYSTEM TUMOR IN MOHAMMAD HOESIN GENERAL HOSPITAL - Henry Sugiharto; Yunni Diansari; Sheila Stephanie Chandra (JURNAL KEDOKTERAN DAN KESEHATAN, 2020)
Pain is one of the cardinal symptom in tumor patient, especially in Central Nervous System (CNS) tumor. It often impacts patient’s quality of life. The incidence and characteristic of pain have rarely been reported in Palembang, Indonesia. This observational study was planned to investigate the clinical presentation and epidemiology of CNS tumor firstly diagnosed in ward throughout July to December 2018. 99 patients recently diagnosed with CNS tumor were enrolled. From 99 patients, we found 34 patients with tumor associated pain. We further evaluated the information of pain linked with brain tumors via questionnaire and medical record. Of all 34 subjects, the age ranged from 43 to 79 years old with female : male ratio 3:1. Pain was present 100% in spinal tumor and 54% in brain tumor. Clinical characteristics of pain found in brain tumor were typically in ipsilateral lesion (92%), pulsating (76%), moderate intensity (60%), recurrent (84%), not radiating (80%), with frequency of 3-4 times in a week (48%). On the other hand, pain in spinal tumor was generally felt on the site of the lesion (100%), radiating (77.8%), electrical type of pain (44.4%), high intensity (77.8), and constant (88.9%). From this study we conclude that tumor locations can show some different pain characteristics. Therefore careful pain assessment is compulsory to have better understanding and more appropriate management.